Segmental in vivo vertebral motion during functional human lumbar spine activities - Li, Guoan (Springer-Verlag, 2009)
Quantitative data on the range of in vivo vertebral motion is critical to enhance our understanding of spinal pathology and to improve the current surgical treatment methods for spinal diseases. Little data have been reported on the range of lumbar vertebral motion during functional body activities. In this study, we measured in vivo 6 degrees-of-freedom (DOF) vertebral motion during unrestricted weightbearing functional body activities using a combined MR and dual fluoroscopic imaging technique. Eight asymptomatic living subjects were recruited and underwent MRI scans in order to create 3D vertebral models from L2 to L5 for each subject. The lumbar spine was then imaged using two fluoroscopes while the subject performed primary flexion-extension, left-right bending, and left-right twisting. The range of vertebral motion during each activity was determined through a previously described imaging-model matching technique at L2-3, L3-4, and L4-5 levels. Our data revealed that the upper vertebrae had a higher range of flexion than the lower vertebrae during flexion-extension of the body (L2-3, 5.4 ± 3.8°; L3-4, 4.3 ± 3.4°; L4-5, 1.9 ± 1.1°, respectively). During bending activity, the L4-5 had a higher (but not significant) range of left-right bending motion (4.7 ± 2.4°) than both L2-3 (2.9 ± 2.4°) and L3-4 (3.4 ± 2.1°), while no statistical difference was observed in left-right twisting among the three vertebral levels (L2-3, 2.5 ± 2.3°; L3-4, 2.4 ± 2.6°; and L4-5, 2.9 ± 2.1°, respectively). Besides the primary rotations reported, coupled motions were quantified in all DOFs. The coupled translation in left-right and anterior-posterior directions, on average, reached greater than 1 mm, while in the proximal-distal direction this was less than 1 mm. Overall, each vertebral level responds differently to flexion-extension and left-right bending, but similarly to the left-right twisting. This data may provide new insight into the in vivo function of human spines and can be used as baseline data for investigation of pathological spine kinematics.